2012
DOI: 10.1074/jbc.m112.414029
|View full text |Cite
|
Sign up to set email alerts
|

MUNC13-4 Protein Regulates the Oxidative Response and Is Essential for Phagosomal Maturation and Bacterial Killing in Neutrophils

Abstract: Background: MUNC13-4 regulates vesicular trafficking, and its deficiency causes immunodeficiency in humans. Results: MUNC13-4 regulates ROS production, phagosomal maturation, and bacterial killing in neutrophils. Conclusion: MUNC13-4 is essential for the neutrophil-dependent innate immune response. Significance: This study identifies MUNC13-4 as a potential target for therapeutic intervention during bacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(89 citation statements)
references
References 69 publications
0
88
1
Order By: Relevance
“…However, it has recently been demonstrated that (1) NK cell cytotoxicity has a distinct immunoregulatory role in HLH disease, 19 and (2) Munc13-4 has a critical function in platelets and neutrophils. [20][21][22][23] By using an LV coding for a Munc13-4/GFP fusion protein, our present study demonstrated that gene transfer into murine HSCs resulted in transgene expression in all the hematopoietic lineages, including NK and myeloid cells. Thus, HSC gene correction (providing multilineage Munc13-4 expression) might be a valuable treatment option for FHL3 in patients.…”
Section: Discussionmentioning
confidence: 94%
“…However, it has recently been demonstrated that (1) NK cell cytotoxicity has a distinct immunoregulatory role in HLH disease, 19 and (2) Munc13-4 has a critical function in platelets and neutrophils. [20][21][22][23] By using an LV coding for a Munc13-4/GFP fusion protein, our present study demonstrated that gene transfer into murine HSCs resulted in transgene expression in all the hematopoietic lineages, including NK and myeloid cells. Thus, HSC gene correction (providing multilineage Munc13-4 expression) might be a valuable treatment option for FHL3 in patients.…”
Section: Discussionmentioning
confidence: 94%
“…Despite its characterization as a Rab27a effector, Munc13-4 regulates important Rab27a-independent functions including the modulation of the secretion of readily releasable secretory vesicles (12), phagosomal maturation (15), and the differential secretory response to stimuli of lytic granules (16). To determine whether Munc13-4 mediates any regulatory function by binding to Rab GTPases other than Rab27a, we developed a screening approach to identify new binding partners of Munc13-4.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the similarity of this phenotype with that observed in Rab27a-deficient patients along with pull-down studies, protein-protein interaction, and functional assays, Munc13-4 was identified as a Rab27a-specific effector (14). Despite shared roles in regulating common secretory pathways, Munc13-4 regulates many cellular functions in a Rab27a-independent manner including phagosomal maturation in neutrophils (15), the differential secretory response to stimuli in NK cells (16) and the regulation of readily releasable secretory granules in granulocytes (12). It is therefore unclear how these discrete molecular events during exocytosis are regulated by Munc13-4.…”
mentioning
confidence: 99%
“…In our study, more than 50% of P. stomatis phagosomes recruited specific granules, as visualized by the granule marker lactoferrin. The lactoferrin-positive integrative pattern observed on P. stomatis phagosomes is an indication of granule fusion (31). Host proteins like lactoferrin can sequester iron, an important bacterial nutritional metal, and prevent microbial growth.…”
Section: Discussionmentioning
confidence: 99%